Impact of the Covid-19 pandemic on health services utilization: a cross-sectional study. (20th October 2021) - Isonne, C; Migliara, G; Turatto, F; Mazzalai, E; De Vito, C; Marzuillo, C; Villari, P; Baccolini, V
Abstract: Background: Health services disruption during the COVID-19 pandemic has forced to postpone or cancel most scheduled health visits. Within this context, disadvantaged people may have been suffered the most from the indirect consequences of the emergency. The aim of the study was to quantify the pandemic impact on health services utilization in the Roman population based on the economic, sociodemographic and cultural characteristics. Methods: In January 2021, an online survey was administrated to 640 patients attending a Roman general practitioner. The questionnaire investigated sociodemographic characteristics, working and living conditions, COVID-19 experience, consequences of lockdown or policy responses, and health literacy. A multiple logistic regression model was built to investigate factor associated with a reduction in the healthcare use. Results: Overall, 451 respondents were surveyed. More than 60% were women and mean age was 55 years. In total, 211 patients referred to have cancelled one or more scheduled health visits (14 vaccinations, 60 screening exams, 168 medical examinations and 23 surgeries). At multivariable logistic regression analysis, the loss of at least one visit seemed to be associated with lower perceived wealth (aOR=1.60, 95%CI: 1.07-2.39), pre-existing comorbidities (aOR=1.60, 95%CI: 1.04-2.45), and older age (aOR=1.03, 95%CI: 1.01-1.04). No association was found for sex, education, or health literacy. Conclusions: A few socio-demographic characteristics seemed to identify people that may have suffered the most from the health services disruption during the COVID-19 pandemic, contributing to worsen the existing health inequalities. Future research is needed to devise strategies aimed at containing the negative effects of the pandemic on vulnerable populations. Key messages: The COVID-19 pandemic seemed to have a greater impact on health service utilization among disadvantaged people. The COVID-19 pandemic may have exacerbated health inequalities.